Sexual polyploidization in red clover Poliploidização sexual em trevo vermelho - Carine Simioni (Scientia Agricola, 2006)
Because sexual polyploidization broadens genetic basis and supply plant breeders with more variability for the selection process, it can be useful in red clover breeding. This paper reports results of three crossing cycles, starting from a parental generation of tetraploid red clover plants (female parent), and diploids from the Quiñiqueli cultivar, selected for production of more than 1% of giant pollen grains (male parent) aiming to obtain tetraploid plants to be used in red clover breeding programs. Crosses in the next generations were performed by mutual cross-pollinations. Chromosome number chimerism and high pollen sterility were detected in F1, F2 and F3, but there was a trend towards increasing seed production and seed viability along the generations, probably due to successful competition between fertile and sterile gametes. The identification of fertile triploids, as well as their recurrent formation along the generations, indicates that triploid block is not complete in red clover, and that triploids may be successfully used as a bridge for the production of sexual polyploids. Porque a poliploidização sexual amplia a base genética e proporciona aos melhoristas maior variabilidade para o processo de seleção, ela pode ser uma ferramenta útil ao melhoramento de trevo vermelho. Com o objetivo de obter plantas tetraplóides que possam ser utilizadas em programas de melhoramento de trevo vermelho, este trabalho relata resultados de três ciclos de cruzamentos, partindo de uma população parental de plantas tetraplóides de trevo vermelho, como genitores femininos, e de diplóides da cultivar Quiñiqueli, selecionados para produção de mais de 1% de grãos de pólen gigantes, como genitores masculinos. Nas outras gerações, os cruzamentos foram realizados por polinizações cruzadas mútuas. Quimerismo para número cromossômico e alta esterilidade de pólen foram detectados em F1 , F2 e F3, mas houve uma tendência para aumento da produção e viabilidade das sementes ao longo das gerações, provavelmente devido à competição bem sucedida entre gametas férteis e estéreis. A identificação de triplóides férteis, assim como sua formação recorrente ao longo das gerações, indica que o bloco triplóide não é completo em trevo vermelho e que triplóides podem ser utilizados com sucesso para a produção de poliplóides sexuais.